Accounting for Mismatch in Low- and Middle-Income Countries : Measurement, Magnitudes, and Explanations - Handel, Michael J.; Valerio, Alexandria; Sánchez Puerta, Maria Laura (Washington, DC: World Bank, 2016)
To stimulate economic advancement, low- and middle-income countries need well-educated and trained workforces to fill the types of skilled jobs that drive economic growth. Improving educational quality and attainment and providing better training are all rightly put forth as policy recommendations to leverage economic growth and job creation. However, new findings based on large scale surveys of adult skills from the World Bank Group’s STEP (Skills toward Employment and Productivity) Skills Measurement Program suggest that many workers are overqualified for their current jobs (based on the education those jobs require). The results of this study suggest that countries may not reap as much benefit from their investments in quality education and training if weak job creation leaves workers’ skills underutilized.